Cattle production systems in the derived savannah and southern Guinea savannah regions of Oyo state, southern Nigeria - Jode, A. de; Reynolds, L.; Matthewman, R.W. (Springer, 1992)
A single visit questionnaire survey was undertaken on 50 cattle owners in Oyo state, south western Nigeria. Data were collected on grazing patterns, calving dates, calf mortalities and attitudes to the N'Dama breed and its crosses with Bunaji cattle. All cattle herds had similar grazing patterns, using natural pasture from April to November, crop residues in December, pasture regrowth after burning plus crop residues in January and regrowth and browse in February and March. The conception pattern was unimodal, reaching a peak in July after the new grass growth from the first rains. Calf mortalities were highest between 2 to 4 months of age during the early rainy season, but were lower in mixed N'Dama/Bunaji herds than in the Bunaji herds. Most cattle owners were interested in purchasing N'Dama breeding stock, believing them to be more productive. This is a move away from the traditional pastoralists practice of keeping only Bos indicus breeds.